Utilização de serviços de fisioterapia em municípios com alta cobertura da estratégia saúde da família - Oliveira, Monica Holanda de (2013)
This is an analysis of the pattern of utilization of health services, important theme in the literature in the areas of policy, planning and management. Through this type of study we obtain indirect information about the access of health services, highlighting elements for the maintenance or repair of health policies. Aimed to characterize the use of physical therapy services for adults and seniors in the city of Praia Grande, SP. We conducted cross-sectional study, based population through household survey. The sampling technique was to conglomerates, which were adopted as primary and secondary units of sampling, respectively, the census sector and the household. The draw for the 40 sectors was done by SPSS software, with the probability of the draw is proportional to the number of residents of the same, a household was selected and it was made from the distribution of enrollment and other households. All residents of selected households were asked to answer the survey. Questionnaires were administered through netbooks operating system designed specifically for this purpose. The system was composed of 10 modules designed to capture and data persistence. 659 households were visited in which 1011 residents responded to the questionnaire. The prevalence of physical therapy in the past 12 months was 3%. 66,7% have a salary range 1-3 minimum wages, 86.7% own their own homes. 37% were seen by the public sector and 63% by private health system. It was found that access to physiotherapy service is still restricted mainly to the poorest segment of the population. The female uses more to physiotherapy services and this county had greater use of the use of physical therapy by the private health system.